Pemahaman Aspek Testing Models dan Purpose of Models Siswa Peminatan MIPA SMA Negeri Se- Kabupaten Brebes - Fenny Roshayanti; Ipah Budi Minarti; Sofia Sofia (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2021)
In studying science, scientific thinking and modeling are needed, with this model development exercise students can have the ability to describe or skills in communicating a target or material according to their creativity and innovation. Nature of Models (NoM) are the properties that exist in the model. This study aims to determine the understanding of the Nature of Models of students who specialize in Mathematics and Natural Sciences in Senior High Schools in Brebes Regency on the aspects of Testing Models and Purpose of Models. The subjects in the study were 334 grade XI students of SMA Negeri in Brebes. This research use desciptive qualitative approach. The instruments used were observation sheets, interviews and tests of understanding of Nature of Models (NoM). The results showed that the students' understanding of Nature of Models in the Testing Models aspect was lower with an average value of 44.15 compared to the Purpose of Models aspect with an average score of 69.86. The factors that influence students 'understanding of the Nature of Models are the use of models as less varied media, teacher learning models that do not develop students' modeling skills.